Quorum sensing inhibition by South African medicinal plants species: an in vitro and an untargeted metabolomics study - Phanankosi Moyo; Olusola Bodede; Madelien Wooding; Ibukun M. Famuyide; Fikile N. Makhubu; Ndivhuwo K. Khorommbi; Michael Ofori; Cynthia A. Danquah; Lyndy J. McGaw; Vinesh J. Maharaj (BMC Complementary Medicine and Therapies)
Abstract Background The emergence of antimicrobial resistance (AMR) is imperiling global health, hence, the need to remedy this challenge by discovering new therapeutic strategies and agents. Quorum sensing inhibition (QSI) is opined as a potential novel strategic approach in the fight against AMR by abrogation of bacterial virulence and pathogenicity. Currently, there are no clinically approved QSI drugs. Based on this, this study evaluated the QSI properties of South African plant species. Methods Twenty-nine extracts and their corresponding 203 fractions generated using solid phase extraction were screened for QSI activity in vitro against Chromobacterium violaceum ATCC 12472. Active and inactive fractions of the most potent plant species were analysed using UPLC-HRMS. The acquired mass spectral data was subjected to chemometric analysis. Results From the QSI assays, three plant species showed remarkable QSI activity, measured by dose-dependent inhibition of violacein production (IVP), at sublethal concentrations. Terminalia phanerophlebia emerged as the most active species, with the extract and five of its fractions showing good activity in IVP (IVP IC50 ≤ 0.1 mg/mL). This was closely followed by Momordica cardiospermoides whose crude extract and two of its corresponding fractions showed good activity (IVP IC50 ≤ 0.1 mg/mL). Three fractions of Helichrysum odoratissimum also had good activity (IVP IC50 ≤ 0.1 mg/mL) marking it one of the most potent selected species. Chemometric analysis identified five compounds including olivetol and hydroxytyrosol as chemical markers positively associated with the QSI activity of T. phanerophlebia. Conclusion In conclusion, the findings of our study provided insight into the QSI properties of South African plant species. Further studies will focus on the isolation of the putative active compounds and the in vitro evaluation of their QSI activity.